The effects of an assignment that incorporated reading, writing, discourse, and reflection for Honors Advanced Algebra students: A quasi-experimental study - Cutts, Anna Denson (My University, 2018)
This quasi-experimental design, with a mixed methods approach, examined the effects of an assignment that incorporated reading, writing, discourse, and reflection for Honors Advanced Algebra students. A sample of 150 Honors Advanced Algebra students and two teachers were the participants of the study. The purpose of the quantitative part of the design was to determine if there was a significant increase in scores on a posttest after Honors Advanced Algebra students solved homework assignments, in Brightspace, algebraically (control group) or by using strategies of reading and writing, discourse, and reflection (treatment group). It was determined that students in the treatment group performed higher on the post-test. Additional quantitative elements of this study were measured by surveys (pre and post), given to student and teacher participants, to determine student and teacher attitudes towards learning and teaching with the assignment. There were statistically significant changes in student attitudes. Specifically, students felt that the assignment helped them to better understand the lessons in the unit. Qualitative elements of this study were measured by open-ended questions on the surveys (pre and post) for students and teachers and teacher interviews. The qualitative elements determined student and teacher suggestions for improving learning and teaching with the assignment. The conclusions from this study contribute to an increasing body of research on how to implement reading, writing, discourse, and reflection in mathematical assignments.
Chapter I INTRODUCTION 1 -- Statement of the Problem 3 -- Theoretical Framework 4 -- Research Questions 7 -- Methodology 8 -- Significance of the Study 9 -- Definitions of Key Terms 10 -- Limitations 12 -- Organization of the Study 13 -- Chapter II REVIEW OF THE LITERATURE 15 -- Critical Thinking in Mathematics 18 -- Mathematical Communities 18 -- Constructivism 21 -- Persuasive Pedagogy 23 -- Communication in Mathematics 24 -- Reading and Writing 24 -- Discourse 29 -- Reflection 35 -- Implications for Mathematics Instruction 38 -- GSE 38 -- Traditional Mathemetics Instruction 40 -- Applying Teaching Practices in Mathematical Communication 43 -- Improving Mathematics Instruction 44 -- Summary 47 -- Chapter III METHODOLOGY 48 -- Research Questions 48 -- Methodology 49 -- Population and Sample 51 -- Instrumentation 53 -- Validity 57 -- Reliability 58 -- Data Collection 59 -- Data Analysis 61 -- Protection of Human Subjects 66 -- Summary 67 -- Chapter IV RESULTS 69 -- Participants… 70 -- Presentation and Analysis of Data 71 -- Phase 1: Pre/Post-test (Quantitative) 72 -- Research Question 1. 73 -- Phase II: Pre/Post Student and Teacher Surveys (Quantitative and Qualitative) 74 -- Research Question 2. 74 -- Quantitative Data… 75 -- Qualitative Data… 88 -- Research Question 3 91 -- Phase III: Teacher Interviews (Qualitative) 93 -- Research Question 4 93 -- Summary 94 -- Chapter V DISCUSSION 99 -- Purpose of the Study 99 -- Related Literature 100 -- Methods 104 -- Limitations 109 -- Summary of the Findings 110 -- Research Question 1 111 -- Research Question 2 113 -- Research Question 3 118 -- Research Question 4 119 -- Discussion 119 -- Implications of the Results 121 -- Recommendations for Future Research 124 -- Summary 125 -- REFERENCES 128 -- APPENDIX A: Treatment Group/Brightspace Homework Assignments 139 -- APPENDIX B: Control Group/Brightspace Homework Assignments 142 -- APPENDIX C: Honors Advanced Algebra Unit 1 Test (PRE/POSTTEST) 144 -- APPENDIX D: Attitudes of Students (Pre) Survey 147 -- APPENDIX E: Attitudes of Students (Post) Survey 149 -- APPENDIX F: Attitudes of Teachers (Pre) Survey 151 -- APPENDIX G: Attitudes of Teachers (Post) Survey 142 -- APPENDIX H: Teacher Interview Guide 155 -- APPENDIX I: IRB Consent To Participate Approval 157 -- APPENDIX J: IRB Parent Consent Approval 161 -- APPENDIX K: Treatment group comments left by students on the post-survey 165 -- APPENDIX L: Control group comments left by students on the post-survey 170 -- APPENDIX M: Comments left by teachers on the post-survey 175 -- APPENDIX N: Comments left by teachers on the teacher interview guide 177.
Keywords: Dissertations, Academic--United States; Algebra; Mathematics; Education; Reading